Experiencing an extensionist action of the academic leagues in the itinerary of the student of Medicine (Research, Society and Development, 2022)
An Academic League is formed, primarily, by students and professors of a certain course (or courses), united by the common interest of developing activities of teaching, research, extension, culture and / or affirmative policies in several areas of academic formation. This study aims to report the importance of health leagues in the construction of the formative itinerary, especially, based on an experience report from the construction of the 1st Academic League Symposium of Recôncavo of Bahia, with the main theme “Interconnecting the Children's Health” highlighting childhood as a stage of the life cycle that requires socio-cultural, political-economic and individual transformations. For this purpose, 15 Academic Leagues, mostly with medical students, were divided into groups to coordinate the event's activities: conferences, courses, practical stations and presentations of scientific papers. Providing students with the competence of an autonomous and critical-reflexive professional with the capacity to meet the population's health demands, striving for the articulation of attitudinal knowledge and skills to act at different levels of health care. The result of this experience shows that developing activities that enable student protagonism where students can exercise skills such as leadership, management, communication and teamwork are fundamental for both the growth of the university and the development of students, in order to deal with future challenges, making the Leagues tools of important value in the academic itinerary of the student in the health field.